Getting the best out of single case data - Jimmie Leppink (Revista Española de Educación Médica)
This article analyzes the value of single-case designs (SCDs) in the fields of personalized healthcare and education, highlighting their growing relevance in research with small samples. In these designs, the same subjects are repeatedly assessed based on the same outcomes, which offers methodological advantages but also poses statistical challenges.